Warfarin and the Risk of Death, Stroke, and Major Bleeding in Patients With Atrial Fibrillation Receiving Hemodialysis: A Systematic Review and Meta-Analysis - Lei, Hong; Yu, Li-Ting; Wang, Wei-Ning; Zhang, Shun-Guo (Frontiers in Pharmacology, 2018)
Background: Up to date, the efficacy and safety of warfarin treatment in atrial fibrillation patients receiving hemodialysis remains controversial. So we performed this meta-analysis to try to offer recommendations regarding warfarin management in this population. Methods: We searched Pubmed, Embase and Cochrane library and reviewed relevant reference lists from 1980 through March 2018. Studies were included if they described the risk of mortality, stroke and bleeding events with or without warfarin in atrial fibrillation patients receiving hemodialysis. Results: Overall, the use of warfarin was not associated with mortality (OR: 0.95, 95%CI: 0.89-1.02), stroke (OR: 1.06, 95%CI: 0.87-1.30) and ischemic stroke (OR: 0.85, 95%CI: 0.68-1.05), but its use could increase the risk of hemorrhagic stroke (OR: 1.34, 95%CI: 1.13-1.59) and major bleeding (OR: 1.24, 95%CI: 1.14, 1.35). In subgroup analyses, when analyses were mainly restricted to atrial fibrillation patients who were undergoing hemodialysis and taking other anticoagulation agents, warfarin therapy was not associated with mortality (OR: 0.98, 95%CI: 0.68-1.42) and ischemic stroke (OR: 1.03, 95%CI: 0.89-1.19), but significantly increase the risk of stroke (OR:1.14, 95%CI: 1.01-1.29) and bleeding events such as hemorrhagic stroke (OR: 1.42, 95%CI: 1.14-1.77) and major bleeding (OR: 1.24, 95%CI: 1.14-1.35). While in patients who didn’t take other anticoagulation agents or aspirin, there was no association in all-cause mortality (OR=0.90, 95% CI 0.78 to 1.04) and stroke among warfarin users and non-warfarin users (OR=1.00, 95% CI 0.71 to 1.40), but it did decrease the risk of ischemic stroke (OR=0.71, 95% CI 0.60 to 0.85) and had no negative impact on hemorrhagic stroke (OR=1.45, 95% CI 0.83 to 2.55). Besides, another subgroup analysis showed that warfarin didn’t exert a protective role in the patients with almost normal lipid levels (OR=1.04, 95% CI 0.85 to 1.26), but seemed to decrease the risk of ischemic stroke in patients with hyperlipidemia (OR=0.38, 95% CI 0.11 to 1.29). Conclusion: Our results suggested that it was necessary to prescribe warfarin for the prevention of ischemic events in hemodialysis patients with atrial fibrillation, but if these patients were already prescribed with other anticoagulants for the treatment of other co-existing diseases, then warfarin was not recommended.